PENGACAKAN CITRA DIGITAL DENGAN METODE TRANSFORMASI FIBONACCI DAN LUCAS - Ginting, Riah Ukur; Hutagalung, Dini M (STMIK Budi Darma, 2018)
The image is a function of 2 (two) dimensions f (x, y), where x and y are the coordinates that show the space, and the value of f (x, y) is called the image intensity at the coordinates. Digital image is an image that has a limited value of x, y, f (x, y). Digital images consist of a limited number of elements, where each element has coordinates and values. These elements are called pixels (Gonzalez and Woods., 2007). One method of randomization in the image is Arnold Transformation where the image is transformed using a cat map, which is a 2x2 matrix. After transformation, the value of each pixel gets new coordinates until the image does not have its original shape. As a result of the above problems, the author uses the basis of Arnold Transformation, to change the value of the map paint with Fibonacci and Lucas series for designing this application so that the randomization results have a higher level of security. The purpose of this study is (1) to do digital image randomization using Fibonacci and Lucas transforms so that the image does not have its original shape anymore and (2) save the randomized images into storage memory. The benefits of this study are (1) the design of digital image randomization applications, so that image security increases and (2) the effectiveness of the Fibonacci and lucas transformation methods in digital image randomization.Keywords: Image Processing, Fibonacci and Lucas